2021
DOI: 10.3390/diagnostics11081376
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota: A Major Player in the Diagnosis of Systemic Diseases

Abstract: The oral cavity is host to a complex and diverse microbiota community which plays an important role in health and disease. Major oral infections, i.e., caries and periodontal diseases, are both responsible for and induced by oral microbiota dysbiosis. This dysbiosis is known to have an impact on other chronic systemic diseases, whether triggering or aggravating them, making the oral microbiota a novel target in diagnosing, following, and treating systemic diseases. In this review, we summarize the major roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 287 publications
(322 reference statements)
0
29
0
4
Order By: Relevance
“…Human oral microbiota has become a new research focus area, as oral bacteria, bacterial products, and inflammatory molecules can invade the human body through the bloodstream or the digestive tract. In this context, it was shown that perturbation of the oral microbiota is associated with not only infectious oral diseases but also with several systemic diseases [ 14 ], such as metabolic diseases, cardiovascular diseases, respiratory diseases, rheumatoid arthritis, inflammatory bowel diseases, Alzheimer’s disease, and autism spectrum disorders [ 15 , 16 ]. For instance, the pathogen in chronic periodontitis, porphyromonas gingivalis , was identified in the brain of Alzheimer’s disease patients and may play a role in the pathogenesis of this illness [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human oral microbiota has become a new research focus area, as oral bacteria, bacterial products, and inflammatory molecules can invade the human body through the bloodstream or the digestive tract. In this context, it was shown that perturbation of the oral microbiota is associated with not only infectious oral diseases but also with several systemic diseases [ 14 ], such as metabolic diseases, cardiovascular diseases, respiratory diseases, rheumatoid arthritis, inflammatory bowel diseases, Alzheimer’s disease, and autism spectrum disorders [ 15 , 16 ]. For instance, the pathogen in chronic periodontitis, porphyromonas gingivalis , was identified in the brain of Alzheimer’s disease patients and may play a role in the pathogenesis of this illness [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saliva constitutes the external environment of the oral cavity and is an important biological sample for the study of oral microbiota, which is a major research focus of the National Institutes of Health Human Microbiome Project ( 16 , 17 ). An imbalance of oral microbiota can not only cause various oral diseases but is also closely related to the development of tumors, diabetes, rheumatoid arthritis, cardiovascular diseases, and nervous system diseases ( 6 ). Changes in microflora community composition can lead to immune-mediated diseases by affecting immune system activation ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of MG is complex and involves an imbalance of gut microbiota ( 4 , 5 ). Because most gut microorganisms originate in the oral cavity ( 6 , 7 ), oral microbiota may also contribute to MG pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…They contain numerous different molecules being the result of metabolic processes taking place at the site of infection, including both those derived from the host and those produced by inhabiting microorganisms. Any change in the delicate balance between the host and its microbiome, or the appearance of a new component in the latter, may be reflected in the subtle differentiation in the set of metabolites found in the niche analyzed ( Na et al., 2021 ; Thomas et al., 2021 ). Possibly, the analysis of changes in the amount of certain metabolites could give information about the rate and direction of the development of periodontal disease and enable monitoring the treatment process; however, it still requires further extensive research, given the significant impact of systemic diseases on the composition of this fluid and the fact that results of studies on different patient groups are often contradictory ( Nguyen et al., 2020 ; Baima et al., 2021 ).…”
Section: Influence Of Periodontal Biofilm Formation On Diagnosis and Treatmentmentioning
confidence: 99%